Applying adaptive qos-aware medium access control in priority-based vehicular ad hoc networks - Chrysostomou, Chrysostomos; Lambrinos, Lambros; Djouvas, Constantinos (My University, 2011)
his paper proposes a novel, adaptive medium access control mechanism for vehicular ad hoc networks. A simple, effective, and efficient nonlinear control law is built, based on fuzzy logic control principles, which can be easily adopted in different network environments (e.g. vehicle-to-vehicle (V2V) communication and vehicle-to-infrastructure (V2I) communication). We demonstrate, via simulative evaluation, that the proposed fuzzy control methodology offers inherent robustness with effective control of the system under dense and dynamic conditions, without the need to (re)tune any parameters. The proposed approach offers distinct differentiation among differently prioritized traffic types, thus providing adequate Quality of Service (QoS) in terms of throughput performance, in contrast with the IEEE 802.11p MAC protocol we compared against.
Keywords: Ad hoc networks (Computer networks); Adaptive control systems; Communication; Fuzzy logic